(untitled) (Heteroglossia – studia kulturoznawczo-filologiczne, 2023)
This paper gives an overview of the theoretical underpinnings and current work in Critical Discourse Analysis (CDA). It defines CDA as a transdisciplinary, text-analytical approach to critical social research, aimed at revealing the power imbalance reflected in the use of language and patterns of dominance imposed through the use of language. Describing the most important schools and models in CDA, the paper demonstrates how critical approaches draw on recent developments in different areas of linguistics, such as pragmatics, cognitive linguistics and corpus studies. At the same time, it shows how the interdisciplinary research agenda of CDA attracts the ‘classic’ theories and tools of linguistics to new empirical territories in political/public discourse. The final part of the paper illustrates the explanatory power of the legitimization-proximization model in CDA in a case study of the discourse of the war-on-terror.